Strategies to Develop Students' Higher Order Thinking Skills in Reading Class - Ainia Mega Rusdiana; Mauly Halwat Hikmat (EDULANGUE, 2020)
This study aims to investigate the strategies used by the teacher to develop students’ higher thinking skills in reading class, and to describe the problems faced by the students. This descriptive qualitative study collected the data from various resources, English teaching learning process, English teacher, students, and lesson plan, garnered through field notes, interviews, and documentation. The data were analyzed using data reduction, data display, and conclusion. The empirical evidence showed that the strategies used by the English teachers topromote the students’ higher thinking skills were making prediction, activating the students’ schemata, drawing inference and encouraging questions. Another finding also indicated that the primary problem encountered by the students was a lack of vocabulary to comprehend the given texts. Recommendation and implication are discussed.